Heracles - Base de données bibliographique sur le sport et l'education physique
The computerized documentation on Sport was installed in France in 1984 with the creation of the SPORTDOC national network that produces HERACLES, the sport and physical education database. Since then, this associative network spreading all over the country has ensured and coordinated in particular, without interruption the processing of 500 magazines (2 third in French language and one third in foreign languages).